ARL Annual Salary Survey 2024 - Mian, Anam (Association of Research Libraries, 2025)
The ARL Annual Salary Survey 2024 reports salary data for all professional staff working in ARL libraries including librarians and nonlibrarian professionals. The Association of Research Libraries is a membership organization of libraries and archives in major public and private universities in Canada and the US, as well as US federal government agencies and large public institutions. ARL is a forum for the exchange of ideas and a catalyst for collective action to create, share, and sustain our global knowledge. The Research and Analytics program, which produces the Salary Survey, pursues a research agenda for the Association, collecting and analyzing data on all aspects of research libraries’ roles in scholarly and scientific production, learning facilitation and learner success, and knowledge access and sustainability. The ARL Annual Salary Survey is the most comprehensive and thorough guide to current salaries in large US and Canadian academic and research libraries and is a valuable management and research tool. Data for 11,256 professional staff members were reported this year for the 118 ARL university libraries, including their law and medical libraries (866 staff members reported by 71 medical libraries and 675 staff members reported by 73 law libraries). For five of the seven nonuniversity ARL members, data were reported for 2,040 professional staff members.
Keywords: ARL; Association of Research Libraries